Kondisi Sosial Ekonomi Masyarakat Petani Kelapa di Desa Matuting Tanjung Kecamatan Gane Timur Tengah Kabupaten Halmahera Selatan - Darling Surya Alnursa (Jurnal Ilmiah Wahana Pendidikan, 2022)
Indonesia is classified as a developing country which always shows that the contribution of the agricultural sector to national economic growth always occupies a very vital position, because Indonesia is known as a country that has very large natural resources in the agricultural sector. North Maluku is one area that has a large potential for agricultural products, especially coconut. This research was conducted in Matuting Tanjung Village, East Gane District, South Halmahera Regency. The research method used is survey method with qualitative research type. The research analysis used is descriptive qualitative analysis and quantitative statistical analysis. Qualitative descriptive analysis is an analytical technique with the intention of describing data, while quantitative statistical analysis is an analysis of a collection of facts that can reveal a problem with a statistical formula